Cylindrical array design to optimize polar-azimuthal direction-finding resolution - Liu, Jinjian; Wong, Kainam Thomas; Wu, Yue Ivan (Applied acoustics, 2025)
The cylindrical array grid provides azimuthal centrosymmetric symmetry, as well as an adjustable elevational resolution that can be refined by a suitable grid along the cylinder's height. For any preset spatial resolution for polar/elevational direction finding and for any mandated optimal array compactness, this paper proposes a design procedure to devise a uniform array grid on the cylinder's lateral surface (given an allocated number of sensors), trading off between the azimuth-polar angle resolution versus the cylinder's compactness. This action-able system-design procedure is based on new insights obtained here from the cylindrical array's Cramér-Rao bounds, derived in a closed mathematical form for the first time in the research literature. •An optimal design procedure to devise a cylindrical array based on the closed-form Cramer Rao Bound analysis.•A new design procedure to maximize directional resolution without considering array compactness.•A new design procedure to optimize array compactness subject to preset thresholds on the directional resolution.